2018
DOI: 10.3390/ma12010091
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Helium Effect on the Microstructure of Nanocrystalline Body-Centered Cubic Iron

Abstract: Helium (He) effect on the microstructure of nanocrystalline body-centered cubic iron (BCC-Fe) was studied through Molecular Dynamics (MD) simulation and simulated X-ray Diffraction (XRD). The crack generation and the change of lattice constant were investigated under a uniaxial tensile strain at room temperature to explore the roles of He concentration and distribution played in the degradation of mechanical properties. The simulation results show that the expansion of the lattice constant decreases and the sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The initial model was relaxed using conjugate gradient minimization at 0 K. Then the intergranular distribution of He was introduced into the models, since the He atom at GB was a key factor affecting the mechanical properties of nanocrystalline Fe [17]. For simplicity, the "GB He" represents He atoms located at the GB region of nanocrystalline Fe hereinafter.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial model was relaxed using conjugate gradient minimization at 0 K. Then the intergranular distribution of He was introduced into the models, since the He atom at GB was a key factor affecting the mechanical properties of nanocrystalline Fe [17]. For simplicity, the "GB He" represents He atoms located at the GB region of nanocrystalline Fe hereinafter.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…GIXRD was also used to detect the microstructure of Heirradiated nanochannel W films [16], and it was observed that the lattice swelling is lower Crystals 2021, 11, 532 2 of 9 in nanochannel W films than that in bulk W due to the He atoms that are released in the former. He effects on the microstructure of nanocrystalline BCC Fe was studied by simulated X-ray diffraction (XRD) [17], showing that the crack generation has a close relationship with the change in the lattice constant during loading. These studies show that the XRD method is reliable to study He effect on the microstructure of nuclear structural material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, various materials (such as W [47][48][49][50], addition of Rh in W [51], use of bcc Fe [52,53], Ta [54], W-Ta [55], Ta/Fe [56], Pd [57], nanocrystalline Cu [58], SiOC/Crystalline Fe nanocomposite [59], W-K [60], reduced activation steel [61], ferritic [62], ferritic/martensitic steels [63], Be pebbles [64][65][66][67], Be and beryllides [68], graphite, carbon fiber composite [69]) and high Z atoms (Zr, No, Mo, Hf, Ta) [70] have been tested but none proved satisfactory [71][72][73][74]. All show rapid surface degradation exhibiting surface blisters [75][76][77][78] and formation of fuzz [51,[79][80][81][82] or under dense nanostructure [40] after bubble.…”
Section: Introductionmentioning
confidence: 99%
“…This is followed up by a detailed MD simulation by Xu et al, that explores the role of He generation on both grain boundary stability and crack growth in BCC-Fe. This modeling effort also takes advantage of recent advancements in computational code to produce simulated X-Ray Diffraction (XRD) patterns that permit rapid experimental validation [11].…”
mentioning
confidence: 99%